DYNAMICS OF CARTILAGE DEGRADATION IN OSTEOARTHRITIS AND REACTIVE ARTHRITIS: COMP-BASED TREATMENT MONITORING - Ziyodullayeva Rukhsora; Toshpulatova Madina (Bright Mind Publishing, 2026)
Osteoarthritis (OA) and reactive arthritis (ReA) represent two clinically and pathophysiologically distinct joint disorders that nonetheless converge on a common outcome: progressive cartilage degradation and structural joint damage. Osteoarthritis is traditionally classified as a degenerative joint disease driven by mechanical stress, aging, and metabolic factors, whereas reactive arthritis is an immune-mediated inflammatory condition that develops following infection. Despite these differences, both diseases ultimately involve disruption of cartilage homeostasis, leading to pain, functional limitation, and reduced quality of life. Understanding and monitoring cartilage degradation dynamics across these conditions remains a major challenge in rheumatology.
Keywords: monitoring cartilage degradation dynamics; homeostasis, leading to pain, functional limitation